2023
DOI: 10.3389/fonc.2023.1169189
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of 18F-PSMA-1007 PET/CT in predicting pathological upgrading of newly diagnosed prostate cancer from systematic biopsy to radical prostatectomy

Abstract: ObjectiveThis study aimed to evaluate predictors for upgrading of newly diagnosed prostate cancer from systematic biopsy (SB) to radical prostatectomy (RP) using fluorine-18 prostate-specific membrane antigen 1007 (18F-PSMA-1007) positron emission tomography/computed tomography (PET/CT) and association with clinical parameters.Materials and methodsWe retrospectively collected data from biopsy-confirmed prostate cancer (PCa) patients who underwent 18F-PSMA-1007 PET/CT prior to RP from July 2019 and October 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Staging PSMA PET/CT of high-risk PCa patients detects lymph node metastases for almost a third of the patients and bone metastases for a sixth of the patients, as reported in a recent review ( 25 ). The estimates fit with recent literature ( 6 - 14 ). So staging PSMA shows metastatic PCa for half of the high-risk patients.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Staging PSMA PET/CT of high-risk PCa patients detects lymph node metastases for almost a third of the patients and bone metastases for a sixth of the patients, as reported in a recent review ( 25 ). The estimates fit with recent literature ( 6 - 14 ). So staging PSMA shows metastatic PCa for half of the high-risk patients.…”
supporting
confidence: 74%
“…Other studies reported that staging PSMA PET/CT gave a similar or slightly higher frequency of patients with miN1/miM1 ( 6 - 14 ). Zheng et al showed that staging PSMA PET/CT gave pathological upgrading for 27% of the patients and a downgrading for 23% of the patients ( 6 ). In a study by Donswijk and coauthors, an upstaging for N/M status was found in 23%/13% while downstaging was found in 9%/23% ( 15 ).…”
mentioning
confidence: 79%